1983
DOI: 10.1080/00288233.1983.10427036
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of records of a Perendale flock V. Repeatabilities and genetic correlations between ages

Abstract: Repeatabilities of greasy fleece weight (FW), staple length (SL), mean fibre diameter (FD), quality number (QN), fleece character (FC), and number of Iambs weaned (NL W) were calculated by regressing older records on younger records in data collected from a flock of Perendale ewes. Average repeat abilities of the wool traits were: FW, 0.62; SL, 0.50; FD, 0.71; QN, 0.46; and FC, 0.18. The repeat abilities of the various components of NL W were low. Genetic correlations between records of each trait collected at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…On the other hand several authors have investigated the effect of ewe age on wool production, various wool characteristics, and litter size (e.g. E ikje 1975; L ewer et al 1983; A tkins 1986; A tkins 1990; G ates and U rioste 1995). The studies indicated that genetic correlations between fleece weights recorded at early ages (1 or 2 years old) and fleece weights recorded at higher ages are different from one.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand several authors have investigated the effect of ewe age on wool production, various wool characteristics, and litter size (e.g. E ikje 1975; L ewer et al 1983; A tkins 1986; A tkins 1990; G ates and U rioste 1995). The studies indicated that genetic correlations between fleece weights recorded at early ages (1 or 2 years old) and fleece weights recorded at higher ages are different from one.…”
Section: Introductionmentioning
confidence: 99%